Lipid-sugar interaction: Relevance to anhydrous biology - CAFFREY, MARTIN (American Society of Plant Biologists, 1988)
The ability of seeds and other anhydrous plant forms to survive the withdrawal of water must involve a mechanism for protecting the integrity of cellular membranes. Evidence from animal systems implicates sugars as protective components, and we have tested the changes in mesomorphic phase state of phospholipid model membranes upon hydration and dehydration in the presence of sucrose and/or sucrose plus raffinose. X-ray diffraction studies of dry dimyristoylphosphatidylcholine (DMPC) indicate that the presence of sucrose lowers the chain order/disorder transition temperature to that of hydrated lipid; likewise, the lamellar repeat spacings showed the dry DMPC/sucrose mixture to be similar to that of the hydrated lipid. These results support the proposed potential of sugars to substitute for water in biomembranes. If sucrose is to serve as a protectant during desiccation of seeds, its tendency to crystallize would lessen its effectiveness. Raffinose is known to serve as an inhibitor of sucrose crystallization, and is abundant in seeds. The addition of raffinose to make DMPC/sucrose/raffinose mixtures (1/1/0.3 mass ratio) prevented sucrose crystallization, suggesting this as a possible in vivo role for raffinose.
PUBLISHED
Keywords: Physical chemistry; lipids